Students’ Mastery of English Grammar towards Effective Writing and Speaking Competence - Sacal, Patrick Glenn Y.; Potane , Joel D. (Future Science / FSH-PH Publications, 2023)
English language proficiency is one of the most pressing issues, particularly in the field of education. Speaking and writing are two of the most important macroskills to master, especially in today's increasingly connected world. The current study seeks to ascertain students' comprehension and mastery of English grammar and explores whether grammar explains the students' proficiency in speaking and writing in Grade 10 Junior High School. The respondents were chosen for the study using a simple random sampling design. Additionally, the researcher's questionnaire, with three qualified validators tested for validity and a pilot tested for reliability, produced a satisfactory Cronbach's alpha result and served as the basis for gathering the study's data. Findings show that students' competence in English grammar, writing, and speaking is satisfactory. The outcome demonstrates that mastery of English grammar accounts for developing an acceptable level of speaking and writing abilities. The study concluded that students' command of English grammar explains their writing and speaking abilities.